Post-Adoption Satisfaction and Policy Demand Paradox among Household Solar Users in Ladakh - Shah, Immad A; Para, Irshad Ahmad; Zargar, Rafia N; Bashir, Ishtiyaq; Peer, Quadri Javed Ahmad (Indian Journal of Extension Education, 2026)
The study aimed to identify factors that influence satisfaction after-adoption and explain why households continue to request government support despite owning functional solar systems. Using a quantitative cross-sectional design, primary data were collected in 2025 from 440 selected solar-adopting households in Ladakh through a primary field study. A structured questionnaire captured demographic, financial, attitudinal, technical, and environmental variables. The analysis employed Principal Component Analysis (PCA) to extract latent constructs, logistic regression to determine predictors of policy demand, and K-means clustering to segment adopters into behavioural groups. The results showed that financially stable and highly satisfied households unexpectedly exhibit the strongest demand for continued subsidies, while financially constrained users report lower satisfaction but have limited policy influence. Three clusters emerged: Happy Rent-Seekers, Contented Independents, and Struggling Dissatisfied, revealing subsidy capture by wealthier users. The study concluded that universal subsidies contribute to inequitable resource distribution and recommends shifting toward targeted, performance-based support, enhanced maintenance services, and improved post-adoption monitoring. This research contributed novel empirical evidence on post-adoption dynamics in high-altitude regions, highlighting the need for policy frameworks that align financial support with household needs.